Polarization Beam Splitter Based on the Gold Wire-Filled Dual-Core Photonic Crystal Fiber at the Communication Wavelengths. Issue 1 (2nd January 2021) - Zhang, Yongxia; Qu, Yuwei; Yuan, Jinhui; Wang, Haiyun; Zhou, Xian; Huo, Jiahao; Yan, Binbin; Wu, Qiang; Wang, Kuiru; Long, Keping; Yu, Chongxiu
ABSTRACT: In this paper, a polarization beam splitter (PBS) based on the gold wire-filled dual-core photonic crystal fiber is proposed. The full-vector finite element method is used to investigate the influences of the fiber structure parameters on the transmission characteristics and coupling length. By appropriately adjusting the fiber structure parameters, the coupling length ratio of 2:1 can be achieved at wavelengths 1.55 and 1.31 μm, so the incident light can be well separated into the two beams with orthogonal polarization states. When the fiber length is 805.3 μm, the maximum extinction ratio ( ER ) within bandwidth of 60 nm is −132.12 dB at wavelength 1.55 μm. When the fiber length is 1264.9 μm, the maximum ER within bandwidth of 70 nm is −197 dB at wavelength 1.31 μm. By optimizing the fiber structure parameters, a PBS with a length of 249.12 μm, the maximum ER of −112.2 dB, and bandwidth of 120 nm can be obtained.